Oedipus tyrannos - Sophocles,Wertenbaker, Timberlake (Bloomsbury, 2013)
'Oedipus Tyrannos' begins the Theban trilogy. The king of Thebes' investigation into the cause of the plague on his city uncovers a terrible and personal secret. Timberlake Wertenbaker's translation of Sophocles' trilogy of Theban plays was premiered by the Royal Shakespeare Company, Stratford upon Avon, in 1991, under the collective title of 'The Thebans'.
10.5040/9780571285334.00000008
Keywords: Drama; Oedipus (Greek mythology)